Lipase-catalyzed synthesis of canola phytosterols oleate esters as cholesterol lowering agents - Villeneuve, Pierre,; Turon, F.; Caro, Y.; Escoffier, R.; Barea, Bruno; Barouh, B.; Lago, R.; Piombo, Georges; Pina, Michel (Enzyme and Microbial Technology, 2005)
Corresponding author. E-mail address: villeneuve@cirad.fr International audience The feasibility of lipase-catalyzed esterification of canola phytosterols with oleic acid was established. The influence of various reactions parameters was evaluated. Among the tested lipases, namely plant lipases from Carica papaya, Ricinus communis (castor bean lipase) or microbial lipases from Rhizomucor miehei, Candida antarctica B or Candida rugosa, the latter appeared to be the most appropriate resulting in a overall production of steryl ester of 38.5% within 24 h in non-optimized conditions whereas esterification degree with other lipases did not exceed 15% in the same conditions. Selecting C. rugosa lipase for any further experiments, it was observed that the nature of the acyl donor was of paramount importance with direct esterification with fatty acids giving better results than transesterification with methyl esters. Similarly, the influence of substrates molar ratio was also checked and a 1:3 excess of fatty acids was shown to be the best. Finally, others parameters such as optimal enzyme load (5%) or temperature (35 ◦C) were determined to allow a final production of steryl esters close to 85% after 72 h.